STUDI ETNOEKOLOGI MASYARAKAT DANI-BALIEM DAN PERUBAHAN LINGKUNGAN DILEMBAH BALIEM, JAYAWIJAYA, IRIAN JAYA - Purwanto, Y (Research Center for Biology-Indonesian Institute of Sciences, 2003)
The objective of the ethnoecology study of the Dani-Baliem society is to know the relationship between Dani-Baliem society and their environment.This study covers the perception and traditional management system of environment by the Dani-Baliem society, and also the impact of their activities to the environment change in Baliem Valley. This study is expected to determine the change of plant diversty, which happened, and to reconstruct this change from pre-historic era to the present time.The methods used in this study based on anthropological, ecological, paleoecological and bibliography study.The result showed the ecosystem change in the Baliem valley since 26.000 BP.It was indicated by Carbon content as a result of fired activities in the base of valley sedimentation.Since 7000 years ago, the impact of human activities in the Baliem valley area is significant. It is indicated by organic material sedimentation.This environment change continue untill now and relate to the intensity of human activities intervention. These human activities cause many enironment units which has physical and biological characteristics. By using floristic analysis in each environment unit, it can be seen the change of plant diversity composition in this area.